Biologically-induced precipitation of aluminium in synthetic acid mine water. (15th May 2017) - Falagán, Carmen; Yusta, Iñaki; Sánchez-España, Javier; Johnson, D. Barrie
Graphical abstract: Highlights: Aluminium was precipitated as hydroxysulfate minerals in a sulfidogenic reactor. Sulfate-reducers use protons present in AMD coupled to the oxidation of glycerol. The aluminium hydroxysulfates that formed were felsöbányaite and hydrobasaluminite. 80% of the aluminium present in the synthetic mine water was removed. The microbial community was dominated by Desulfosporosinus acididurans . Abstract: Concentrations of aluminium in acidic waste waters are frequently much higher than in circum-neutral pH water bodies, and can represent a significant environmental hazard. In very low pH (<2.0) aqueous solutions, aluminium is present as a free cation Al 3+, whereas it forms complexes with hydroxyl ions in moderately acidic and circum-neutral pH waters. Acidic waters associated with metal mining are usually enriched with sulfate, which complexes with aluminium to form hydroxysulfates as felsöbányaite (also known as basaluminite) or hydrobasaluminite. An anaerobic bench-scale reactor, populated with a mixed community of acid-tolerant sulfate-reducing and other bacteria and maintained at pH 5.0, was fed with synthetic acid (pH 2.5/3.0) mine water containing varying concentrations of aluminium. The sulfate-reducing bacteria utilized protons released during the formation of solid-phase hydroxysulfate minerals from soluble aluminium, as well as those present in the acidic feed liquor, to reduce sulfate, coupling this to the oxidation of glycerol. The aluminium hydroxysulfates that formed into the bioreactor were identified as hydrobasaluminite and felsöbányaite. The planktonic microbial community in the bioreactor was dominated by the acid-tolerant sulfidogen Desulfosporosinus acididurans, together two species of facultatively anaerobic acidophiles ( Acidocella aromatica and Acidithiobacillus ferrooxidans ) that do not reduce sulfate to hydrogen sulfide. This study confirmed the hypothesis that sulfate-reducing bacteria can mediate the precipitation of aluminium in acidic mine waters as hydroxysulfate minerals, and provided evidence in support of this process being responsible for this as a natural attenuation process in environments such as pit lakes in the Iberian Pyrite Belt and elsewhere.